A case study of the Nottingham University Malaysia Campus students: exploring students’ perceptions on opening a cinema on university campus - Tleuzhanova, Kamilla (2013)
Nowadays there are lots of universities located far from the main cities. As a result, university campuses have lack of entertainment, which is one of the important aspects of students’ life. One of the main leisure activities is cinema, which is believed to be the best remedy for stress and depression. Thus, the aim of this dissertation is to find out the viability of opening cinema on university campus, concentrating on different types of cinema, preferences in genre and possible motivations and barriers of cinema attendance. The research work was based on the review of relevant literature and empirical data collected through focus group interviews. This research work produced the number of significant findings: the preferred type of cinema on campus is either indoor or open-air cinema; the preferred types of movies can be of any genre, ranging from comedies to horror movies; the preferred price should be less than market price; students’ erratic attendance may be influenced by different motivations (movie, to relief the stress) and barriers (study, campus environment, movie). The main conclusion that is drawn from the following study is that it is viable to open cinema on campus with a remote location if the factors discusses above are considered and taken into account.